Financial Technologies: A Note on Mobile Payment - Song Yee Leng; Ameen Talib; Ardi Gunardi (Jurnal Keuangan dan Perbankan, 2018)
The financial market is currently disrupted by the rise of new technologies "FinTech” a short form for financial technology, which profoundly reshapes the financial intermediary structure and makes financial services more efficient. Mobile technology with Internet-enabled devices is the next logical phase of the World Wide Web campaign such as mobile phone taking over the mass market and will fundamentally change the way products are bought and sold as well as financial services especially the mobile payment system. This research examines changes payment method in financial services, particularly those involving mobile payments that can create new channels for consumers to purchase goods and services using a mobile phone. Mobile payment application is ready to replace traditional cash, checks, credit and debit card throughout the country. In this stage of development, the current situation of mobile payment market, review the previous literature on mobile payment services, analysis use of mobile payment worldwide and various initiatives use mobile phones to offer financial services for those ‘unbanked’.JEL Classification: G20, O14DOI: https://doi.org/10.26905/jkdp.v22i1.1993